Give a bee a bad name . . - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The dominance of the notorious 'killer' bee - an Africanized form of the European honey-bee Apis mellifera - may be better news for the bee-keepers if South and Central America than they realize. Recent research suggest this species may well be the...